Perancangan dan Pengembangan Aplikasi Absensi Berbasis Kotlin yang Terintegrasi dengan Website Backoffice Menggunakan Rest API Laravel - Arkan, Faiz; Aziz Zuama, Robi; Setia Budi, Eko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The attendance system is a fundamental aspect of managing employee presence in both corporate and educational institutions. Conventional methods that rely on manual attendance, such as paper-based records or spreadsheets, have numerous limitations. These weaknesses include susceptibility to data manipulation, time-consuming data recap processes, and lack of system integration. This study develops a digital attendance system based on Android using the Kotlin programming language, integrated with a BackOffice website through a REST API built on Laravel. The development methodology used is the Waterfall model, which is systematic and well-suited for projects with clearly defined requirements. The REST API serves as a communication bridge between the mobile application and the web system, utilizing the JSON format over the HTTP protocol. System testing results show that the application can manage attendance data in real-time, automatically validate location, and provide a web interface for administrators to monitor employee attendance. The system also integrates the Google Drive API to store photo evidence of attendance in a cloud-based environment. Through this approach, the study contributes to the development of an efficient, transparent, and scalable attendance system.